The Developing Sense of Place - Bette Tryon; Walt Tryon (Oz, 1984)
Place has intuitive meaning, assigned value, and is associated with experiences linking self with the environment. Place, the possession and personalization of an environmental setting, reflects the values and predispositions we have grown with and continue to develop...